2005
DOI: 10.1021/es0480668
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Sensors Powered by Microbial Fuel Cells

Abstract: Monitoring parameters characterizing water quality, such as temperature, pH, and concentrations of heavy metals in natural waters, is often followed by transmitting the data to remote receivers using telemetry systems. Such systems are commonly powered by batteries, which can be inconvenient at times because batteries have a limited lifetime and must be recharged or replaced periodically to ensure that sufficient energy is available to power the electronics. To avoid these inconveniences, a microbial fuel cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
151
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(155 citation statements)
references
References 27 publications
1
151
0
Order By: Relevance
“…In addition, small biofuel cells show promise over batteries or solar cells for applications such as powering autonomous sensors or sensor networks (7)(8)(9)(10). Many homeland security, military, and medical applications for miniature sensors make recharging or replacing batteries impossible, while other applications may require power sources to function in environments where there is limited or no sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, small biofuel cells show promise over batteries or solar cells for applications such as powering autonomous sensors or sensor networks (7)(8)(9)(10). Many homeland security, military, and medical applications for miniature sensors make recharging or replacing batteries impossible, while other applications may require power sources to function in environments where there is limited or no sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…The electricity production by MFC technology as of currently when compared with methanogenic anaerobic digestion falls short of economical (Logan 2004). The operating temperature also acts as a limitation for MFC technology as microbial reactions cease at temperatures below 20°C (Shantaram et al 2005). There are several factors involved in determining the efficiency of MFC technology namely, technical factors such as internal resistance, electrode potential and oxygen availability, which act as a hindrance in elevating the potential of MFC technology on a commercial and economical basis (Logan & Regan 2006).…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
“…Dissolved oxygen (DO) is crucial for the cathodic reaction, and therefore SMFC is typically installed in shallow waters [118]. Previous studies have demonstrated that SMFCs can produce electricity and supply power to wireless sensors in both marine and fresh-water environments [113,119,120]. Capacitors have been adopted to accumulate energy generated from MFCs [121][122][123][124].…”
Section: Bes For Agricultural Monitoringmentioning
confidence: 99%
“…They can be installed in wetlands, rivers or lakes near the farmland. To use the electricity, the output potentials must be boosted and operated by DC-DC converters and a PMS [119,120]. In the area where open water is not available, soil MFCs [130][131][132][133] or plant MFCs [134,135] may be applied.…”
Section: Bes For Agricultural Monitoringmentioning
confidence: 99%